Graphene composite material magnetic conductive adhesive as well as preparation method and application thereof

Through the use of graphene composite magnetic permeable rubber, the problems of poor magnetic permeability and low adhesiveness of existing magnetic permeable rubber have been solved, and efficient electromagnetic performance improvement and inductance increase are achieved. It is suitable for bonding and packaging of chip common mode inductors and other electronic components.

CN119912891APending Publication Date: 2025-05-02XIAN RUICI ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110976.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When used in electronic products, existing magnetic permeability has poor magnetic permeability, low viscosity, and the addition of certain materials will affect the inductance.

Method used

Graphene composite magnetic adhesive is used, and its raw materials include 10%~15% graphene, 65%~80% ferrite magnetic powder, as well as appropriate amounts of binders, curing agents, diluents, anti-settling agents and defoaming agents. Through efficient grinding and dispersion processes, uniform dispersion of graphene and ferrite magnetic powder in the colloid is ensured.

Benefits of technology

It significantly improves the permeability and bonding strength of magnetic permeability, improves the electromagnetic performance of electronic components, reduces product defect rate, improves production efficiency, and achieves an inductance increase of 30% to 45%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912891A_ABST
    Figure CN119912891A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnetic conductive adhesives, and discloses a graphene composite material magnetic conductive adhesive and a preparation method and application thereof.The graphene composite material magnetic conductive adhesive is prepared from, by mass, 10%-15% of graphene, 65%-80% of ferrite magnetic powder, 2%-10% of binder, 1%-5% of curing agent, 1%-2% of diluent, 0-1% of anti-settling agent and 0.1%-1% of defoaming agent; wherein the graphene adopts single-layer nano oxidized and reduced graphene; the ferrite magnetic powder adopts nickel-zinc soft magnetic ferrite magnetic powder, and comprises the following main components: 66.60%-68.35% of Fe2O3; the content of ZnO is 22.25% to 22.80%; 7.05%-8.05% of NiO and the balance of CuO. The doping components comprise MoO3, CaCO3, V2O5 and Nb2O5, the content of MoO3 accounts for 0.06%-0.10% of the mass of the main components, the content of CaCO3 accounts for 0.01%-0.04% of the mass of the main components, and the content of V2O5 accounts for 0.03%-0.07% of the mass of the main components; and the content of Nb2O5 is 0.02%-0.07% of the mass of the main component. According to the magnetic conductive glue of the graphene composite material, the magnetic conductivity of the glue is improved, the surface hardness and the bonding strength are improved, and the magnetic conductive glue is durable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic conductive adhesives, and specifically relates to a graphene composite material magnetic conductive adhesive and a preparation method and application thereof, and is mainly used in the production and manufacture of chip common mode inductors. Background Art

[0002] Magnetic adhesive is a special adhesive that has magnetic fillers added to it to give it magnetic properties. It is widely used in industries such as radio and instrumentation to bond magnetic components such as transformers, inductors, magnetic antennas, and coil cores. The main functions of magnetic adhesive include bonding and insulation, of which bonding is mainly used to fix magnetic materials together, while insulation is used to prevent contact between magnetic particles, thereby reducing eddy current losses in the magnetic medium and improving the quality factor. However, as electronic products continue to move towards miniaturization, electronic components such as chip inductors, small magnetic antennas, and digital tape drive heads, in addition to refined process requirements, must also use magnetic adhesives for bonding and packaging to meet the use requirements of device miniaturization, high sensitivity, and wide temperature range.

[0003] At present, magnetic adhesives are mainly made by adding carbonyl iron powder or iron-silicon-aluminum iron powder to adhesives (epoxy type) to give the adhesives certain magnetic properties. However, due to the small particle size and high density of iron powder, it is easy to agglomerate in the adhesive, resulting in poor magnetic properties and low adhesion of the magnetic adhesive; if materials such as silicon oxide and aluminum oxide are added, its inductance will be seriously affected. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a graphene composite material magnetic conductive glue and its preparation method and application, to overcome the shortcomings of the prior art, and can be applied to chip common mode inductors and chip pulse transformers, to improve the electromagnetic properties of electronic components, greatly reduce product defective rates, improve production efficiency, and ultimately enable mass production.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A graphene composite material magnetic conductive adhesive, whose raw materials include, by mass percentage: 10%-15% graphene, 65%-80% ferrite magnetic powder, 2%-10% binder, 1%-5% curing agent, 1%-2% diluent, 0-1% anti-settling agent, and 0.1%-1% defoaming agent; The graphene is a single-layer nano-oxidation-reduction graphene; and the ferrite magnetic powder is nickel-zinc soft ferrite magnetic powder.

[0006] Preferably, the composition of the ferrite magnetic powder includes a main component and a doping component in terms of mass percentage; The main components include: Fe2O3: 66.60% to 68.35%; ZnO: 22.25% to 22.80%; NiO: 7.05% to 8.05%, and the balance is CuO; The doping components include MoO3, CaCO3, V2O5 and Nb2O5, among which the content of MoO3 is 0.06% to 0.10% of the mass of the main component, the content of CaCO3 is 0.01% to 0.04% of the mass of the main component, the content of V2O5 is 0.03% to 0.07% of the mass of the main component; the content of Nb2O5 is 0.02% to 0.07% of the mass of the main component.

[0007] Preferably, the preparation process of the ferrite magnetic powder includes: The Fe2O3 powder, ZnO powder and NiO powder are ball-milled and mixed to obtain a mixture A; Drying the mixed material A; Pre-burning and drying the dried mixed material A to obtain material B; Add the doping component to material B, perform ball milling and mixing, and then dry to obtain mixed material C; Granulating and pressing the mixed material C to obtain a sample ring blank; The sample ring blank is sintered to obtain ferrite.

[0008] Preferably, Fe2O3 powder, ZnO powder and NiO powder are ball-milled and mixed to obtain mixed material A, wherein the weight ratio of zirconium ball: ultrapure water: powder is 6: (1.4-1.6): 1, the ball milling speed is 100-300 r / min, and the wet ball milling mixing time is 3-6 h; When the dried mixed material A is pre-burned and dried to obtain material B, the pre-burning temperature is controlled at 900-940°C, the pre-burning time is 90-150 minutes, and the pre-burning atmosphere is air; After adding the doping component to material B, ball milling and mixing are performed, and then drying is performed to obtain mixed material C, and the ball milling time is controlled at 5.5-6.5h; The mixed material C is granulated and pressed to obtain a sample ring blank, and polyvinyl alcohol glue is added to the mixed material C for granulation, the mass of the polyvinyl alcohol glue is 8% to 12% of the mass of the mixed material C, and the granulation particle size is 120 to 250 μm; during pressing, 0.14 wt% of zinc stearate by weight of the powder is added to the granulated powder as a release agent, and the molding method adopts bidirectional pressurized cold pressing molding, and the molding pressure is 10 MPa; When the sample ring blank is sintered, a gradient temperature rise process is adopted, specifically including: first heating to 450°C at 1.3~1.7°C / min, keeping warm for 2h, then heating to 900°C at 2.8~3.5°C / min, and then heating to 1100~1170°C at 1.8~2.2°C / min, keeping warm for 2h, and then naturally cooling with the furnace to obtain the ferrite.

[0009] Preferably, the initial magnetic permeability μ of the ferrite powder is i ≥3000@100kHz, Curie temperature T C >100℃.

[0010] Preferably, the binder is epoxy resin or phenolic resin; the curing agent is polyamide or methylimidazole; the diluent is one or more of ethanol, ethyl acetate, butyl acetate and pinene alcohol; the anti-settling agent is hydrophobic nano-silica; the defoaming agent is one or more of polyether-modified silicone oil, modified polyether and modified silicone.

[0011] Preferably, the performance indicators of the graphene composite material magnetic conductive adhesive are as follows: magnetic permeability ≥38, bonding strength ≥80N, and viscosity ≥22000mPa·S.

[0012] The present invention also provides a method for preparing the graphene composite material magnetic conductive adhesive as described above, comprising the following steps: The binder, curing agent, diluent, anti-settling agent and defoaming agent are mixed and ground to obtain a colloid; Adding graphene and ferrite magnetic powder into the colloid and dispersing them evenly, and then grinding them to obtain a magnetic conductive colloid precursor; The magnetic conductive glue precursor is stirred and dispersed while being vacuumed, and then continuously ground to obtain the magnetic conductive glue of the graphene composite material.

[0013] Preferred: The binder, curing agent, diluent, anti-settling agent and defoaming agent are stirred and dispersed at high speed in a constant temperature stirring and dispersing machine to achieve uniform mixing, wherein the high-speed dispersing time is 0.5 to 1 hour and the rotation speed is 100 to 200 r / min; the mixture of the binder, curing agent, diluent, anti-settling agent and defoaming agent is ground on a three-roll mill, the gap of the three-roll mill is adjusted to <2.5 μm, and the grinding times are 2 times; Adding graphene and ferrite magnetic powder to the colloid, and then placing it in a constant temperature stirring disperser for high-speed dispersion, so that the graphene and ferrite magnetic powder are evenly dispersed in the colloid, wherein the high-speed dispersion time is 3 to 6 hours and the rotation speed is 300 to 500 r / min; grinding the uniform mixture of graphene, ferrite magnetic powder and colloid on a three-roll mill, adjusting the gap of the three-roll mill to less than 2.5 μm, and the number of grinding times is 3 times; The magnetic conductive glue precursor is placed in a planetary disperser and vacuumed while being stirred, wherein the vacuuming time is 30 to 60 minutes; and then ground on a three-roll mill, adjusting the gap of the three-roll mill to less than 2.5 μm, and the grinding time is 18 to 48 hours.

[0014] The present invention also provides the use of the graphene composite material magnetic conductive adhesive as described above, wherein the graphene composite material magnetic conductive adhesive is used for bonding and / or packaging magnetic components.

[0015] Compared with the prior art, the present invention has the following beneficial effects: After adding graphene to the magnetic conductive adhesive of the present invention, the magnetic permeability of the magnetic conductive adhesive itself and the magnetic permeability used in the patch common mode inductor are greatly improved. Among them, the graphene added to the magnetic conductive adhesive combines with the nickel in the ferrite magnetic powder, changes the electronic structure of the material, and produces a unique spin property. The rotation of the electron around the axis will generate a tiny magnetic field (i.e., magnetic moment). It is very important that the prepared ferrite magnetic powder is a high-quality material with high magnetic permeability and high performance, which provides sufficient conditions for improving the electromagnetic properties of the magnetic conductive adhesive. In addition, the graphene structure is stable and the material is relatively soft, which improves the torsion damping performance and strengthens the drop resistance; at the same time, the addition of the toughening agent can also improve the cold and heat shock resistance of the material, making the magnetic conductive adhesive durable. The added anti-settling agent hydrophobic nano-silica plays an anti-settling and viscosity-increasing role, so that the viscosity and bonding strength of the magnetic conductive adhesive are improved. Specifically, after testing, the magnetic conductive glue of the graphene composite material of the present invention improves the magnetic permeability of the glue itself, improves the surface hardness and bonding strength, and is durable; its magnetic permeability is ≥38, the bonding strength is ≥80N, and the viscosity is ≥22000mPa·S. The magnetic conductive glue of the present invention is applied to the chip common mode inductor, so that the inductance L of the chip common mode inductor is increased by 30%~45% of the original.

[0016] Furthermore, the ferrite powder of the present invention is a high-performance high-quality material with high magnetic permeability. i ≥3000@100kHz, Curie temperature T c >100℃, which provides sufficient conditions for improving the electromagnetic properties of magnetic conductive adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart of the preparation of the graphene composite material magnetic conductive adhesive; DETAILED DESCRIPTION In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0018] The raw materials of the graphene composite material magnetic conductive adhesive of the present invention include, by mass percentage, 10%-15% of graphene, 65%-80% of ferrite magnetic powder, 2%-10% of binder, 1%-5% of curing agent, 1%-2% of diluent, 0-1% of anti-settling agent, and 0.1%-1% of defoaming agent; wherein the graphene adopts single-layer nano-oxidation-reduction graphene; and the ferrite magnetic powder adopts nickel-zinc soft ferrite magnetic powder.

[0019] The ferrite magnetic powder adopts nickel-zinc high magnetic permeability soft ferrite magnetic powder. The components of the ferrite magnetic powder include main components and doping components. In terms of mass percentage, the main components include: Fe2O3: 66.60% to 68.35%; ZnO: 22.25% to 22.80%; NiO: 7.05% to 8.05%, and the balance is CuO. The doping components include MoO3, CaCO3, V2O5 and Nb2O5, wherein the content of MoO3 is 0.06% to 0.10% of the mass of the main component, the content of CaCO3 is 0.01% to 0.04% of the mass of the main component, the content of V2O5 is 0.03% to 0.07% of the mass of the main component; and the content of Nb2O5 is 0.02% to 0.07% of the mass of the main component.

[0020] The preparation process of the nickel-zinc high magnetic permeability soft ferrite material of the present invention comprises: Fe2O3 powder, ZnO powder and NiO powder are mixed and ball-milled to obtain a mixture A; Drying the mixed material A; Pre-burning and drying the dried mixed material A to obtain material B; Adding trace elements to material B, ball milling, and then drying to obtain mixed material C; Granulating and pressing the mixed material C to obtain a sample ring blank; The sample ring blank is tested after sintering to obtain the high magnetic permeability nickel-zinc soft ferrite material.

[0021] In the above scheme, Fe2O3 powder, ZnO powder and NiO powder are mixed to obtain mixed material A, which is mixed by wet method. During ball milling, the weight ratio of zirconium ball: ultrapure water: powder is 6: (1.4-1.6): 1, the ball milling speed is 100-300r / min, and the wet ball milling mixing time is 3-6h; after ball milling, it is dried at a certain temperature.

[0022] When the mixed material A is pre-fired, the pre-fired temperature is controlled at 900-940° C., the pre-fired time is 90-150 minutes, and the pre-fired atmosphere is air; after adding a trace amount of the material B, the ball milling time is controlled at 5.5-6.5 hours; When the mixed material C is granulated, the amount of polyvinyl alcohol (PVA) glue is controlled to be 8% to 12% of the material C, and the granulation particle size is 120 to 250 μm; When the sample ring is pressed and molded, 0.14 wt% of zinc stearate based on the weight of the powder is added to the granulated powder as a demoulding agent, and the molding method adopts bidirectional pressure cold pressing molding with a molding pressure of 10 MPa.

[0023] When sintering the sample ring blank, a gradient temperature rise process is adopted, specifically as follows: first heat to 450°C at 1.3~1.7°C / min, keep warm for 2h, then heat to 900°C at 2.8~3.5°C / min, then heat to 1100~1170°C at 1.8~2.2°C / min, keep warm for 2h, and then naturally cool in the furnace to obtain the high magnetic permeability nickel-zinc soft ferrite material.

[0024] The performance parameters of the nickel-zinc high magnetic permeability soft ferrite material obtained by the present invention are as follows: initial magnetic permeability μ i ≥3000@100kHz, Curie temperature T C >100℃.

[0025] In the above scheme of the present invention, the binder is epoxy resin (or phenolic resin), CAS No.: 105359-67-9; the curing agent is polyamide (or methylimidazole), CAS No.: 63428-83-1; the diluent is ethanol (or one or more of ethyl acetate, butyl acetate, terpineol, and ethanol); the anti-settling agent is hydrophobic nano-silica, and the defoaming agent is polyether-modified silicone oil (or one or more of modified polyether and modified silicone), CAS No.: 67674-67-3.

[0026] See also Figure 1 The method for preparing the above-mentioned graphene composite material magnetic conductive adhesive of the present invention comprises the following steps: Step 1: Weigh epoxy resin, polyamide, ethanol, hydrophobic nano-silica, and polyether-modified silicone oil, stir and disperse them in a constant temperature stirring disperser, grind them on a three-roll grinder, and adjust the gap between the three-roll grinders to less than 2.5 μm to obtain a colloid; Step 2: Weigh graphene and high-conductivity ferrite magnetic powder, add them to the colloid, place them in a constant temperature stirring disperser for high-speed dispersion, grind them on a three-roll grinder, adjust the gap of the three-roll grinder to <2.5μm, and obtain a magnetic conductive glue precursor; Step 3: Place the magnetic conductive glue precursor obtained in step 2 in a planetary disperser, stir and evacuate, and then continue grinding to obtain an epoxy resin glue with magnetic conductive properties, that is, a magnetic conductive glue of a graphene composite material.

[0027] In the step 1, the high-speed dispersion time is 0.5 to 1 hour, the grinding times are 2 times, and the rotation speed is 100 to 200 r / min; in the step 2, the high-speed dispersion time is 3 to 6 hours, the grinding times are 3 times, and the rotation speed is 300 to 500 r / min; in the step 3, the vacuuming time is 30 to 60 minutes, and the grinding time is 18 to 48 hours.

[0028] The magnetic conductive adhesive of the graphene composite material of the present invention can be applied to the bonding and packaging of magnetic components. The present invention is specifically applied to a common-mode chip inductor. The prepared magnetic conductive adhesive is applied to the common-mode chip inductor, and after being placed in an oven at 120° C. for 30 minutes for curing, its inductance is measured.

[0029] Embodiment 1: The present embodiment provides a method for preparing and applying a graphene composite material magnetic conductive adhesive, comprising the following steps: Step 1: Preparation of magnetic filler-ferrite powder (1) First ball milling: Take Fe2O3 with purity ≥ 99.40%, NiO ≥ 99.20%, and ZnO ≥ 99.70%, and weigh them according to the following ratio: Fe2O3: 67.12wt%; ZnO: 22.32wt%; NiO: 7.71wt%, and the balance is CuO. Put them into a nylon ball mill, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.5:1. The speed is 220r / min, and the ball milling is carried out for 4h. After ball milling, it is dried in a constant temperature box at 80℃ to obtain mixed material A; (2) Pre-burning: When pre-burning the mixed material A, the pre-burning temperature is controlled at 930°C, the pre-burning time is 120 minutes, the pre-burning atmosphere is air, and the material B is obtained after drying; (3) Secondary ball milling: Add trace elements (i.e., doping components) to the material B obtained in step (2) above, and weigh them according to the following ratio of the main components: MoO3: 0.08wt%; CaCO3: 0.02wt%; V2O5: 0.05wt%; Nb2O5: 0.04wt%. Place the material B with the trace elements added in a nylon ball mill for secondary ball milling, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1:1. The speed is 220r / min, and the ball milling is performed for 6h. After ball milling, it is dried at a certain temperature to obtain a mixture C. (4) Granulation: Mixture C was placed in a mortar and ground into powder. 11% PVA glue was added and continued to grind to a certain particle size and then sieved. The obtained material particle size was 120 μm. (5) High temperature gradient sintering: The granulated sample described in step (4) is placed in a sintering furnace and sintered at 1160°C and kept warm for 2 hours. The temperature rise gradient is as follows: from room temperature to 450°C, the temperature is raised at a rate of 1.5°C / min, and kept warm at 450°C for 2 hours. From 450°C to 900°C, the temperature is raised at a rate of 3.5°C / min, and then the temperature is raised to 1160°C at a rate of 1.5°C / min and kept warm for 2 hours. After the temperature is naturally cooled to room temperature, the high magnetic permeability nickel-zinc soft ferrite material sample is obtained. The magnetic permeability of the high magnetic permeability soft ferrite material μ i =3061.07@100kHz, Curie temperature T C =102℃.

[0030] Step 2: Mixing and grinding of binder, curing agent, diluent, anti-settling agent and defoaming agent 10wt% of epoxy resin, 5wt% of polyamide, 1.5wt% of ethanol, 0.8wt% of hydrophobic nano-silica, and 0.2wt% of polyether-modified silicone oil were weighed respectively by mass percentage, stirred for 1h and dispersed at high speed in a constant temperature stirring disperser, and then transferred to a three-roll mill for grinding at a speed of 200r / min for 40min, twice, and the gap between the three-roll mill was adjusted to <2.5μm to obtain a colloid; Step 3: Doping of graphene and magnetic fillers 13.5wt% of graphene and 69wt% of ferrite powder were weighed by mass percentage, added to the colloid in step 2, placed in a constant temperature stirring disperser for high-speed dispersion for 4.5h, and then transferred to a three-roll mill for grinding at a speed of 500r / min for 50min, and the grinding number was 3 times, while continuing to adjust the gap of the three-roll mill to <2.5μm, to obtain a magnetic conductive glue precursor; Step 4: Vacuum stirring and grinding The magnetic conductive glue precursor obtained in step 3 is placed in a planetary disperser and vacuumed for 40 minutes while stirring, and then continued to grind for 36 hours to obtain an epoxy resin glue with magnetic conductive properties, that is, a magnetic conductive glue of a graphene composite material.

[0031] Embodiment 2: The present embodiment provides a method for preparing and applying a graphene composite material magnetic conductive adhesive, comprising the following steps: Step 1: Preparation of magnetic filler-ferrite powder (1) First ball milling: Take Fe2O3 with purity ≥ 99.40%, NiO ≥ 99.20%, and ZnO ≥ 99.70%, and weigh them according to the following ratio: Fe2O3: 66.94wt%; ZnO: 22.40wt%; NiO: 7.25wt%, and the balance is CuO. Put them into a nylon ball mill, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.4:1. The speed is 100r / min, and the ball mill is milled for 3h. After ball milling, dry it in a constant temperature box at 80℃ to obtain mixed material A; (2) Pre-burning: When pre-burning the mixed material A, the pre-burning temperature is controlled at 900°C, the pre-burning time is 90 minutes, the pre-burning atmosphere is air, and the material B is obtained after drying; (3) Secondary ball milling: Add trace elements to the material B obtained in step (2) above, and weigh them according to the following ratio of the main component mass: MoO3: 0.07wt%; CaCO3: 0.03wt%; V2O5: 0.03wt%; Nb2O5: 0.05wt%. Place the material B with added trace elements in a nylon ball mill for secondary ball milling, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.4:1. The rotation speed is 100r / min, and the ball milling is carried out for 5.5h. After ball milling, it is dried in a thermostat at 80℃ to obtain a mixture C. (4) Granulation: Mixture C was placed in a mortar and ground into powder. 8% PVA glue was added and continued to grind to a certain particle size and then sieved. The obtained material particle size was 200 μm. (5) High temperature gradient sintering: The granulated sample described in step (4) is placed in a sintering furnace and sintered at 1100°C and kept at this temperature for 2 hours. The temperature rise gradient is as follows: from room temperature to 450°C, the temperature is raised at a rate of 1.3°C / min, and kept at 450°C for 2 hours. From 450°C to 900°C, the temperature is raised at a rate of 2.8°C / min, and then the temperature is raised to 1100°C at a rate of 1.8°C / min and kept at this temperature for 2 hours. After the temperature is naturally cooled to room temperature, the sample is taken out of the furnace to obtain the high magnetic permeability nickel-zinc soft ferrite material sample. The magnetic permeability of the high magnetic permeability soft ferrite material μ i =3045.88@100kHz, Curie temperature T C =101℃.

[0032] Step 2: Mixing and grinding of binder, curing agent, diluent, anti-settling agent and defoaming agent 9wt% of epoxy resin, 5wt% of polyamide, 2wt% of ethanol, 1wt% of hydrophobic nano-silica, and 0.5wt% of polyether-modified silicone oil were weighed respectively by mass percentage, stirred for 30min in a constant temperature stirring disperser, dispersed at high speed, and then transferred to a three-roll mill for grinding at a speed of 100r / min for 40min, twice, and the gap between the three-roll mill was adjusted to <2.5μm to obtain a colloid; Step 3: Doping of graphene and magnetic fillers 12wt% of graphene and 70.5wt% of ferrite powder were weighed by mass percentage, added to the colloid in step 2, placed in a constant temperature stirring disperser for high-speed dispersion for 3 hours, and then transferred to a three-roll mill for grinding at a speed of 300r / min for 50min, and the grinding number was 3 times, while continuing to adjust the gap of the three-roll mill to <2.5μm, to obtain a magnetic conductive glue precursor; Step 4: Vacuum stirring and grinding The magnetic conductive glue precursor obtained in step 3 is placed in a planetary disperser and vacuumed for 30 minutes while stirring, and then continued to grind for 18 hours to obtain an epoxy resin glue with magnetic conductive properties, that is, a magnetic conductive glue of a graphene composite material.

[0033] Embodiment 3: The present embodiment provides a method for preparing and applying a graphene composite material magnetic conductive adhesive, comprising the following steps: Step 1: Preparation of magnetic filler-ferrite powder (1) First ball milling: Take Fe2O3 with purity ≥ 99.40%, NiO ≥ 99.20%, and ZnO ≥ 99.70%, and weigh them according to the following ratio: Fe2O3: 68.28wt%; ZnO: 22.80wt%; NiO: 8wt%, and the balance is CuO. Put them into a nylon ball mill, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.6:1. The speed is 300r / min, and the ball mill is carried out for 6h. After ball milling, it is dried in a constant temperature box at 80℃ to obtain mixed material A; (2) Pre-burning: When pre-burning the mixed material A, the pre-burning temperature is controlled at 940°C, the pre-burning time is 150 minutes, the pre-burning atmosphere is air, and the material B is obtained after drying; (3) Secondary ball milling: Add trace elements to the material B obtained in step (2) above, and weigh them according to the following ratio of the main component mass: MoO3: 0.09wt%; CaCO3: 0.04wt%; V2O5: 0.06wt%; Nb2O5: 0.06wt%. Place the material B with the trace elements added in a nylon ball mill for secondary ball milling, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.6:1. The rotation speed is 300r / min, and the ball milling is carried out for 6.5h. After ball milling, it is dried at a certain temperature to obtain a mixture C; (4) Granulation: Mixture C was placed in a mortar and ground into powder. 12% PVA glue was added and continued to grind to a certain particle size and then sieved. The obtained material particle size was 250 μm. (5) High temperature gradient sintering: The granulated sample described in step (4) is placed in a sintering furnace and sintered at 1170°C and kept at this temperature for 2 hours. The temperature rise gradient is as follows: from room temperature to 450°C, the temperature is raised at a rate of 1.7°C / min, and kept at 450°C for 2 hours. From 450°C to 900°C, the temperature is raised at a rate of 3°C / min, and then the temperature is raised to 1170°C at a rate of 2.2°C / min and kept at this temperature for 2 hours. After the temperature is naturally cooled to room temperature, the high magnetic permeability nickel-zinc soft ferrite material sample is obtained. The magnetic permeability of the high magnetic permeability soft ferrite material μ i =3027.53@100kHz, Curie temperature T C =100℃.

[0034] Step 2: Mixing and grinding of binder, curing agent, diluent, anti-settling agent and defoaming agent 10wt% epoxy resin, 5wt% polyamide, 1.5wt% ethanol, 0wt% hydrophobic nano-silica, and 1wt% polyether-modified silicone oil were weighed respectively by mass percentage, stirred for 40min in a constant temperature stirring disperser, dispersed at high speed, and then transferred to a three-roll mill and ground at a speed of 150r / min for 40min, twice, and the gap between the three-roll mill was adjusted to <2.5μm to obtain a colloid; Step 3: Doping of graphene and magnetic fillers 15wt% of graphene and 67.5wt% of ferrite powder were weighed by mass percentage, added to the colloid in step 2, placed in a constant temperature stirring disperser for high-speed dispersion for 6 hours, and then transferred to a three-roll mill for grinding at a speed of 400r / min for 50min, and the grinding number was 3 times, while continuing to adjust the gap of the three-roll mill to <2.5μm, to obtain a magnetic conductive glue precursor; Step 4: Vacuum stirring and grinding The magnetic conductive glue precursor obtained in step 3 is placed in a planetary disperser and vacuumed for 1 hour while stirring, and then continued to grind for 48 hours to obtain an epoxy resin glue with magnetic conductive properties, that is, a magnetic conductive glue of a graphene composite material.

[0035] Comparative Example 1: The preparation method and application of the magnetic conductive adhesive of this comparative example include the following steps: Step 1: Preparation of magnetic filler-ferrite powder (1) First ball milling: Take Fe2O3 with purity ≥ 99.40%, NiO ≥ 99.20%, and ZnO ≥ 99.70%, and weigh them according to the following ratio: Fe2O3: 67.12wt%; ZnO: 22.32wt%; NiO: 7.71wt%, and the balance is CuO. Put them into a nylon ball mill, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1.5:1. The speed is 220r / min, and the ball milling is carried out for 4h. After ball milling, it is dried in a constant temperature box at 80℃ to obtain mixed material A; (2) Pre-burning: When pre-burning the mixed material A, the pre-burning temperature is controlled at 930°C, the pre-burning time is 120 minutes, the pre-burning atmosphere is air, and the material B is obtained after drying; (3) Secondary ball milling: Add trace elements to the material B obtained in step (2) above, and weigh them according to the following ratio of the main component mass: MoO3: 0.08wt%; CaCO3: 0.02wt%; V2O5: 0.05wt%; Nb2O5: 0.04wt%. Place the material B with the trace elements added in a nylon ball mill for secondary ball milling, and add zirconium balls and ultrapure water. The weight ratio of zirconium balls: ultrapure water: powder in the ball mill is 6:1:1. The speed is 220r / min, and the ball milling is carried out for 6h. After ball milling, it is dried at a certain temperature to obtain a mixture C. (4) Granulation: Mixture C was placed in a mortar and ground into powder. 11% PVA glue was added and continued to grind to a certain particle size and then sieved. The obtained material particle size was 120 μm. (5) High temperature gradient sintering: The granulated sample described in step (4) is placed in a sintering furnace and sintered at 1160°C and kept warm for 2 hours. The temperature rise gradient is as follows: from room temperature to 450°C, the temperature is raised at a rate of 1.5°C / min, and kept warm at 450°C for 2 hours. From 450°C to 900°C, the temperature is raised at a rate of 3.5°C / min, and then the temperature is raised to 1160°C at a rate of 1.5°C / min and kept warm for 2 hours. After the temperature is naturally cooled to room temperature, the high magnetic permeability nickel-zinc soft ferrite material sample is obtained. The magnetic permeability of the high magnetic permeability soft ferrite material μ i =3061.07@100kHz, Curie temperature T C =102℃.

[0036] Step 2: Mixing and grinding of binder, curing agent, diluent, anti-settling agent and defoaming agent 10wt% of epoxy resin, 5wt% of polyamide, 1.5wt% of ethanol, 0.8wt% of hydrophobic nano-silica, and 0.2wt% of polyether-modified silicone oil were weighed respectively by mass percentage, stirred for 1h and dispersed at high speed in a constant temperature stirring disperser, and then transferred to a three-roll mill for grinding at a speed of 200r / min for 40min, twice, and the gap between the three-roll mill was adjusted to <2.5μm to obtain a colloid; Step 3: Doping of magnetic fillers 81wt% of ferrite powder was weighed by mass percentage, added to the colloid in step 2, placed in a constant temperature stirring disperser for high-speed dispersion for 4.5h, and then transferred to a three-roll mill for grinding at a speed of 500r / min for 50min, and the grinding number was 3 times, while continuing to adjust the gap of the three-roll mill to <2.5μm, to obtain a magnetic conductive glue precursor; Step 4: Vacuum stirring and grinding The magnetic conductive glue precursor obtained in step 3 is placed in a linear disperser and stirred while evacuating for 40 minutes, and then continued to grind for 36 hours to obtain an epoxy resin glue with magnetic conductive properties, that is, a magnetic conductive glue without graphene.

[0037] Comparative Example 2: Ordinary magnetic adhesive The test results of the magnetic conductive adhesive performance of each embodiment and comparative example are shown in Table 1: Table 1

[0038] It can be seen from the various properties of the magnetic conductive adhesives of the above embodiments and comparative examples that the magnetic permeability of the embodiments is ≥38, the viscosity is ≥22000 mPa·s, and the bonding strength is ≥80N. Among the three embodiments, the performance of embodiment 1 is the best, with a magnetic permeability of 42, a viscosity of up to 22800 mPa·s, and a bonding strength of 91N. However, since the two groups of comparative examples do not add the magnetic conductive material (nickel-zinc ferrite material) prepared by the present invention, the magnetic permeability of the magnetic conductive adhesive is relatively low, and the overall performance is relatively poor.

[0039] The magnetic conductive glue obtained in Example 1 was applied to the common-mode inductor of the SMD type, and the glue dispensing needle was controlled to be 0.1 mm. The magnetic conductive glue was applied to the common-mode inductor of the SMD type for bonding, and then placed in a constant temperature box at 120°C for curing for 30 minutes. The inductance improvement rate is shown in Table 2: Table 2

[0040] As can be seen from Table 2, the magnetic conductive glue is applied to six groups of SMD common mode inductors, and the inductance improvement rate can reach up to 45%, and the average improvement rate is more than 39%, and the dispensing rate and smoothness of the six groups of magnetic conductive glue are good. This shows that the physical and chemical properties of the magnetic conductive glue obtained by the present invention are relatively excellent, and the applicability is very good.

[0041] From the above embodiments and comparative examples, it can be seen that the magnetic permeability of the graphene composite material magnetic adhesive of the present invention is ≥38, the bonding strength is ≥80N, the viscosity is ≥22000mPa·S, and the glue dispensing smoothness is good; secondly, the magnetic adhesive of the present invention is applied to the chip common mode inductor, so that its inductance L is increased by 30%~45% on the original basis, overcoming the problems of decreased inductance of the chip inductor after using glue, abnormal automated continuous production, etc., and automated assembly line production can be realized, the product defect rate is extremely low, and the production efficiency is high.

[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that improvements and modifications can be made without departing from the core technology of the present invention, and these improvements and modifications should also fall within the scope of patent protection of the present invention. Any changes within the meaning and scope equivalent to the claims of the present invention should be considered to be included in the scope of the claims.

Claims

1. A graphene composite material magnetic adhesive, characterized in that: In terms of mass percentage, the raw materials include: graphene 10%~15%, ferrite magnetic powder 65%~80%, binder 2%~10%, curing agent 1%~5%, diluent 1%~2%, anti-settling agent 0~1%, defoaming agent 0.1%~1%; The graphene is a single-layer nano-oxidation-reduction graphene; and the ferrite magnetic powder is nickel-zinc soft ferrite magnetic powder.

2. The graphene composite material magnetic conductive adhesive according to claim 1, characterized in that: In terms of mass percentage, the composition of ferrite magnetic powder includes main components and doping components; Among them, the main components include: Fe2O3: 66.60% ~ 68.35%; ZnO: 22.25% ~ 22.80%; NiO: 7.05% ~ 8.05%, and the balance is CuO; The doping components include MoO3, CaCO3, V2O5 and Nb2O5, among which the content of MoO3 is 0.06% to 0.10% of the mass of the main component, the content of CaCO3 is 0.01% to 0.04% of the mass of the main component, the content of V2O5 is 0.03% to 0.07% of the mass of the main component; the content of Nb2O5 is 0.02% to 0.07% of the mass of the main component.

3. The graphene composite material magnetic conductive adhesive according to claim 2, characterized in that: The preparation process of the ferrite magnetic powder includes: The Fe2O3 powder, ZnO powder and NiO powder are ball-milled and mixed to obtain a mixture A; Drying the mixed material A; Pre-burning and drying the dried mixed material A to obtain material B; Add the doping component to material B, perform ball milling and mixing, and then dry to obtain mixed material C; Granulating and pressing the mixed material C to obtain a sample ring blank; The sample ring blank is sintered to obtain ferrite.

4. The graphene composite material magnetic conductive adhesive according to claim 3, characterized in that: Fe2O3 powder, ZnO powder and NiO powder are ball-milled and mixed to obtain mixed material A, and wet mixing is adopted, wherein the weight ratio of zirconium ball: ultrapure water: powder is 6: (1.4-1.6): 1, the ball milling speed is 100-300r / min, and the wet ball milling mixing time is 3-6h; When the dried mixed material A is pre-burned and dried to obtain material B, the pre-burning temperature is controlled at 900-940°C, the pre-burning time is 90-150 minutes, and the pre-burning atmosphere is air; After adding the doping component to material B, ball milling and mixing are performed, and then drying is performed to obtain mixed material C, and the ball milling time is controlled at 5.5-6.5h; The mixed material C is granulated and pressed to obtain a sample ring blank, and polyvinyl alcohol glue is added to the mixed material C for granulation, the mass of the polyvinyl alcohol glue is 8% to 12% of the mass of the mixed material C, and the granulation particle size is 120 to 250 μm; during the pressing and molding, 0.14% of zinc stearate by weight of the powder is added to the granulated powder as a release agent, and the molding method adopts bidirectional pressurized cold pressing molding, and the molding pressure is 10 MPa; When the sample ring blank is sintered, a gradient temperature rise process is adopted, specifically including: first heating to 450°C at 1.3~1.7°C / min, keeping warm for 2h, then heating to 900°C at 2.8~3.5°C / min, and then heating to 1100~1170°C at 1.8~2.2°C / min, keeping warm for 2h, and then naturally cooling with the furnace to obtain the ferrite.

5. The graphene composite material magnetic conductive adhesive according to claim 1, characterized in that: Initial magnetic permeability μ of ferrite powder i ≥3000@100kHz, Curie temperature T C >100℃.

6. The graphene composite material magnetic conductive adhesive according to claim 1, characterized in that: The binder is epoxy resin or phenolic resin; the curing agent is polyamide or methylimidazole; the diluent is one or more of ethanol, ethyl acetate, butyl acetate and pinene alcohol; the anti-settling agent is hydrophobic nano-silica; the defoaming agent is one or more of polyether modified silicone oil, modified polyether and modified silicone.

7. The graphene composite material magnetic conductive adhesive according to claim 1, characterized in that: The performance indicators of the graphene composite material magnetic conductive adhesive are as follows: magnetic permeability ≥38, bonding strength ≥80N, and viscosity ≥22000mPa·S.

8. A method for preparing a graphene composite material magnetic conductive adhesive according to any one of claims 1 to 7, characterized in that: The process includes the following: The binder, curing agent, diluent, anti-settling agent and defoaming agent are mixed and ground to obtain a colloid; Adding graphene and ferrite magnetic powder into the colloid and dispersing them evenly, and then grinding them to obtain a magnetic conductive colloid precursor; The magnetic conductive glue precursor is stirred and dispersed while being vacuumed, and then continuously ground to obtain the magnetic conductive glue of the graphene composite material.

9. The method for preparing a graphene composite material magnetic conductive adhesive according to claim 8, characterized in that: The binder, curing agent, diluent, anti-settling agent and defoaming agent are stirred and dispersed at high speed in a constant temperature stirring and dispersing machine to achieve uniform mixing, wherein the high-speed dispersing time is 0.5 to 1 hour and the rotation speed is 100 to 200 r / min; the mixture of the binder, curing agent, diluent, anti-settling agent and defoaming agent is ground on a three-roll mill, the gap of the three-roll mill is adjusted to <2.5 μm, and the grinding times are 2 times; Adding graphene and ferrite magnetic powder to the colloid, and then placing it in a constant temperature stirring disperser for high-speed dispersion, so that the graphene and ferrite magnetic powder are evenly dispersed in the colloid, wherein the high-speed dispersion time is 3 to 6 hours and the rotation speed is 300 to 500 r / min; grinding the uniform mixture of graphene, ferrite magnetic powder and colloid on a three-roll mill, adjusting the gap of the three-roll mill to less than 2.5 μm, and the number of grinding times is 3 times; The magnetic conductive glue precursor is placed in a planetary disperser and vacuumed while being stirred, wherein the vacuuming time is 30 to 60 minutes; and then ground on a three-roll mill, adjusting the gap of the three-roll mill to less than 2.5 μm, and the grinding time is 18 to 48 hours.

10. The use of a graphene composite material magnetic conductive adhesive according to any one of claims 1 to 7, characterized in that: The graphene composite material magnetic conductive adhesive is used for bonding and / or packaging magnetic components.